A Photo-Crosslinking Approach to Identify Class II SUMO-1 Binders - Kira Brüninghoff; Stephanie Wulff; Wolfgang Dörner; Ruth Geiss-Friedlander; Henning D. Mootz (Frontiers in Chemistry, 2022)
The small ubiquitin-like modifier (SUMO) is involved in various cellular processes and mediates known non-covalent protein-protein interactions by three distinct binding surfaces, whose interactions are termed class I to class III. While interactors for the class I interaction, which involves binding of a SUMO-interacting motif (SIM) to a hydrophobic groove in SUMO-1 and SUMO-2/3, are widely abundant, only a couple of examples have been reported for the other two types of interactions. Class II binding is conveyed by the E67 loop region on SUMO-1. Many previous studies to identify SUMO binders using pull-down or microarray approaches did not strategize on the SUMO binding mode. Identification of SUMO binding partners is further complicated due to the typically transient and low affinity interactions with the modifier. Here we aimed to identify SUMO-1 binders selectively enriched for class II binding. Using a genetically encoded photo-crosslinker approach, we have designed SUMO-1 probes to covalently capture class II SUMO-1 interactors by strategically positioning the photo-crosslinking moiety on the SUMO-1 surface. The probes were validated using known class II and class I binding partners. We utilized the probe with p-benzoyl-phenylalanine (BzF, also termed BpF or Bpa) at the position of Gln69 to identify binding proteins from mammalian cell extracts using mass spectrometry. By comparison with results obtained with a similarly designed SUMO-1 probe to target SIM-mediated binders of the class I type, we identified 192 and 96 proteins specifically enriched by either probe, respectively. The implicated preferential class I or class II binding modes of these proteins will further contribute to unveiling the complex interplay of SUMO-1-mediated interactions.